2020
DOI: 10.1183/13993003.03764-2020
|View full text |Cite
|
Sign up to set email alerts
|

TNF-mediated alveolar macrophage necroptosis drives disease pathogenesis during respiratory syncytial virus infection

Abstract: Respiratory Syncytial Virus (RSV) is the major cause of acute bronchiolitis in infants under 2 years old. Necroptosis has been implicated in the outcomes of respiratory virus infections. Here we report that RSV infection triggers necroptosis in primary mouse macrophages and human monocytes in a RIPK1-, RIPK3-, and MLKL-dependent manner. Moreover, necroptosis pathways are harmful to RSV clearance from alveolar macrophages. Additionally, Ripk3-/- mice were protected from RSV-induced weight loss and presented red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 64 publications
0
51
0
Order By: Relevance
“…Depleting AMs significantly reduces the survival rate and increases lung injury severity. However, some other pathogens, such as Pseudomonas aeruginosa and respiratory syncytial virus (RSV), can induce AM pyroptosis or necroptosis, thereby causing severe inflammation and increasing lung injury severity (68,69). Some intracellular bacteria, such as Mycobacterium tuberculosis, can infect TR-AMs and, thus, mediate the spread of M. tuberculosis from the alveoli to the lungs (70).…”
Section: Infections and Lung Injurymentioning
confidence: 99%
“…Depleting AMs significantly reduces the survival rate and increases lung injury severity. However, some other pathogens, such as Pseudomonas aeruginosa and respiratory syncytial virus (RSV), can induce AM pyroptosis or necroptosis, thereby causing severe inflammation and increasing lung injury severity (68,69). Some intracellular bacteria, such as Mycobacterium tuberculosis, can infect TR-AMs and, thus, mediate the spread of M. tuberculosis from the alveoli to the lungs (70).…”
Section: Infections and Lung Injurymentioning
confidence: 99%
“…Interestingly, hUCB-MSCs were robustly infected after 72 h when compared to ALMs (Figure 1C). We then investigated whether RSV would trigger ALM death as we have previously described for primary AMs [19] by measuring lactate dehydrogenase (LDH) release. ALMs were resistant to RSV-induced lytic cell death over the course of 24 h (Figure 1D).…”
Section: Alms Are Not Productively Infected By Rsv and Are Resistant To Rsv-induced Cell Deathmentioning
confidence: 99%
“…Most of the target genes were enriched in the virus-related signaling pathways, TNF signaling pathway, and IL-17 signaling pathway. Several studies [31][32][33] have demonstrated that the TNF signaling pathway and IL-17 signaling pathway were related to RSV infection. The TNF signaling pathway plays a significant role in immune regulation and inflammation [34].…”
Section: Biomed Research Internationalmentioning
confidence: 99%